Serratiopeptidase reduces the invasion of osteoblasts by Staphylococcus aureus. (December 2017) - Selan, Laura; Papa, Rosanna; Ermocida, Angela; Cellini, Andrea; Ettorre, Evaristo; Vrenna, Gianluca; Campoccia, Davide; Montanaro, Lucio; Arciola, Carla Renata; Artini, Marco
Finding new strategies to counteract periprosthetic infection and implant failure is a main target in orthopedics. Staphylococcus aureus, the leading etiologic agent of orthopedic implant infections, is able to enter and kill osteoblasts, to stimulate pro-inflammatory chemokine secretion, to recruit osteoclasts, and to cause inflammatory osteolysis. Moreover, by entering eukaryotic cells, staphylococci hide from the host immune defenses and shelter from the extracellular antibiotics. Thus, infection persists, inflammation thrives, and a highly destructive osteomyelitis occurs around the implant. The ability of serratiopeptidase (SPEP), a metalloprotease by Serratia marcescens, to control S. aureus invasion of osteoblastic MG-63 cells and pro-inflammatory chemokine MCP-1 secretion was evaluated. Human osteoblast cells were infected with staphylococcal strains in the presence and in the absence of SPEP. Cell proliferation and cell viability were also evaluated. The release of pro-inflammatory chemokine MCP-1 was evaluated after the exposure of the osteoblast cells to staphylococcal strains. The significance of the differences in the results of each test and the relative control values was determined with Student's t-test. SPEP impairs their invasiveness into osteoblasts, without affecting the viability and proliferation of bone cells, and tones down their production of MCP-1. We recognize SPEP as a potential tool against S. aureus bone infection and destruction.